Rancang Bangun Aplikasi Pengelola Keuangan Gereja Berbasis Android: Design and Development of Android-Based Church Financial Management Application - Excelsis Deo Lukow; Xaverius B. N. Najoan; Steven Ray Sentinuwo (Universitas Sam Ratulangi, 2022)
The financial management of GMIM Imanuel Remboken Church is currently done manually, with financial data recorded in books and calculations performed using Excel. The financial information is then printed and copied onto PowerPoint slides for weekly presentations at the church. The issues include separate storage of financial data, the lengthy process of managing and presenting financial reports, difficulties in accessing information for absent church members, and high printing costs. This research aims to create an Android-based church financial management application that can record transactions and deliver financial information to the congregation. The result is an Android-based church financial management application that can be used to manage the funds of the congregation, columns, and BIPRA. The application also establishes new standards for financial reporting in GMIM Imanuel Remboken Church. Based on the research objectives and findings, it can be concluded that the use of the RAD method in developing this application successfully creates a Church Financial Management application that serves as a tool for financial management within the church organization. It is hoped that this application can be implemented in other churches to improve efficiency and accessibility in financial management